The Effect of Apperception on Learning Readiness of Class IV Elementary School Students - Ervi Rahmadani; Arwan Wiratman; Yusdiana Yusdiana (Journal Corner of Education, Linguistics, and Literature, 2022)
The purpose of this study was to determine the effect of apperception on the learning readiness of fifth grade elementary school students. The research was conducted in Soppeng Regency, precisely at UPTD SPF SDN 254 Mappatongai. The type of research used is an experimental quasi-experimental design that uses one group pretest-posttest. The independent variable in this study is the provision of apperception, while the dependent variable is readiness to learn. The population in this study amounted to 47 people. The sampling technique used was random sampling by selecting class IV, which consisted of 12 people as samples. The research instruments used were observation sheets and questionnaires. The results of the data that have been collected, processed qualitatively and quantitatively using the SPSS application. The results of the pretest showed that the average student learning readiness was 62.17 which was in the sufficient category. The results of the observations showed that the students' learning readiness had progressed from the first meeting to the fourth meeting. After the posttest was conducted, it was found that the average student learning readiness was 82.25 which was in the high category. From the results of the research that has been done, it can be concluded that there is an average difference in learning readiness between pretest and posttest of 20.08 and there is an effect of apperception on learning readiness of fifth grade students at UPTD SPF SDN 254 Mappatongai, Soppeng Regency. This is indicated by the value of sig. (2-tailed) is 0.0005 < 0.05, which indicates that H0 is rejected and H1 is accepted.